An in vitro study on the depth of etched enamel using the acid etch technique at different time durations (15, 60 an 90 secs.) - Jacalne, Lalaine
Each of the five samples of polished newly extracted human premolars were sectioned into 3 equal parts, giving a total of 15 specimen. The 3 parts of each tooth sample were treated or etched at 15, 60 and 90 secs. respectively, using 50% Phosphoric acid. The depth of etched enamel rods were measured under the Scanning Electron Microscope (SEM). Data gathered were statistically analysed and it appears that there is a difference on the depth of enamel etched at 15, 60 and 90 secs.